2020
DOI: 10.1093/gigascience/giz166
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analyses reveal distinct genetic architectures and selective pressures in buffaloes

Abstract: Background The domestic buffalo (Bubalus bubalis) is an essential farm animal in tropical and subtropical regions, whose genomic diversity is yet to be fully discovered. Results In this study, we describe the demographic events and selective pressures of buffalo by analyzing 121 whole genomes (98 newly reported) from 25 swamp and river buffalo breeds. Both uniparental and biparental markers were investigated to provide the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 87 publications
3
26
0
Order By: Relevance
“…For the domestication of two other highly successful bovines, the river and the swamp buffalo, we refer to Zhang et al (2020a), Sun et al . (2020) and Luo et al . (2020).…”
Section: Domestication Dispersal and Differentiation Of Breedsmentioning
confidence: 97%
See 1 more Smart Citation
“…For the domestication of two other highly successful bovines, the river and the swamp buffalo, we refer to Zhang et al (2020a), Sun et al . (2020) and Luo et al . (2020).…”
Section: Domestication Dispersal and Differentiation Of Breedsmentioning
confidence: 97%
“…2010) and have been domesticated separately (Sun et al . 2020). Selection targeting the dairy production of the river buffalo and the draught power of the swamp buffalo is likely to have led to divergent domestication traits (Luo et al .…”
Section: Phylogeny and Evolutionmentioning
confidence: 99%
“…Individual Hp values were Z-transformed as: where μHp is the overall average heterozygosity and σHp is the standard deviation for all windows in each subpopulation. To detect putative selected loci in this study, we first calculated the pooled heterozygosity (Hp) and its Z-transformations, ZHp , in sliding 50 KB windows along the scaffolds [ 20 , 21 ]. Putatively selected loci were defined as genetic regions in overlapping windows with extremely low ZHp values (<−7) and extremely high di values (top 1%).…”
Section: Methodsmentioning
confidence: 99%
“…The swamp buffalo is traditionally raised as a draught animal for rice cultivation, and is mainly bred in extensive rural areas in Northeast India, Southeast Asia and South China. Previous studies have reported that the two types of buffalo descended from different wild Asian water buffalo in separate geographical regions [4,5]. The river buffalo was domesticated in the western region of the Indian subcontinent, and then spread to the west.…”
Section: Introductionmentioning
confidence: 99%